Strategic Business Management: A Practical Framework and Causal Model of Empowering Leadership, Team Cohesion, Knowledge-Sharing Behavior, and Team Performance - Kasemsap, Kijpokin (Journal of Social and Development Sciences, 2013)
Research objectives were to determine a practical framework and to create a causal model of empowering leadership, team cohesion, knowledge-sharing behavior, and team performance of petroleum refinery plant employees in Thailand. The study reported the responses of 594 operational employees from seven petroleum refinery plants operating in different parts of Thailand. Data were analyzed with descriptive statistics using SPSS (version 11.5) and path analysis using LISREL (version 8). Research findings indicate that dimensions of empowering leadership, team cohesion, and knowledge-sharing behavior have mediated positive effect on team performance. Knowledge-sharing behavior positively mediates the relationships between empowering leadership and team performance and between team cohesion and team performance. Furthermore, empowering leadership is positively correlated with team cohesion.